Genital region cleansing wipes: Effects on urine culture contamination - Selek, Mehmet Burak; Bektöre, Bayhan; Sezer, Ogün; Kula Atik, Tuğba; Baylan, Orhan; Özyurt, Mustafa (The Journal of Infection in Developing Countries, 2017)
Introduction: Urine culture is the gold standard test for revealing the microbial agent causing urinary tract infection (UTI). Culture results are affected by sampling techniques; improper sampling leads to contamination of urine and thus contamination of the culture with urogenital flora. We aimed to evaluate the effect of urogenital cleansing, performed with chlorhexidine-containing genital region cleansing wipes (GRCW) on contamination rates. Methodology: A total of 2,665 patients with UTI-related complaints and with urine culture requests from various outpatient clinics were enrolled in the study. Of the patients, 1,609 in the experimental group used GRCW before sampling, while 1,046 in the control group did not use any wipes. Results: The contamination rate in the experimental group patients was 7.7%, while it was 15.8% in the control group. Contamination rates were significantly higher in the control group than in the experimental group for both women and men. Contamination rates for children and adults were also significantly lower in the experimental group than in the control group. Conclusions: Our study, conducted in a large population, showed that the use of chlorhexidine-containing cleansing wipes significantly reduced urine culture contamination rates in both genders, in both child and adult age groups. Using GRCW, collection of urine after urogenital area cleansing will decrease the contamination problem.